Magnetism and structural chemistry of the n=2 Ruddlesden-Popper phase La3LiMnO7 - Battle, P; Burley, J; Gallon, D; Grey, C; Sloan, J (2004)
Polycrystalline samples of the n=2 Ruddlesden-Popper phase La 3LiMnO7 have been prepared and characterized. X-ray and neutron diffraction suggest that the structure is tetragonal with a disordered distribution of Li and Mn cations over the octahedral sites, but 6Li MAS NMR shows that the Li and Mn are 1:1 ordered locally. Electron microscopy shows that the stacking of the cation-ordered, perovskite-like bilayers along the crystallographic z-axis is disordered on the distance scale sampled by X-ray and neutron diffraction. Magnetometry data and neutron diffraction data collected at 2K together suggest that the Mn cations within each structural domain order antiferromagnetically at 14K, but that the disorder along z prevents the establishment of long-range magnetic order. © 2003 Elsevier Inc. All rights reserved.